Polarization-independent and high-efficiency broadband optical absorber in visible light based on nanostructured germanium arrays - Zhao, Jiancun; Yu, Xiaochang; Yang, Xiaoming; Tee, Clarence Augustine Teck Huo; Yuan, Weizheng; Yu, Yiting (Optical Society of America, 2019)
A broadband optical absorber based on the nanostructured germanium (Ge) film composed of single-sized circular nanodisk–nanohole arrays is proposed, which demonstrates high efficiency, strong polarization independence, and large viewing angle. Due to the electric and magnetic resonance absorption modes excited by the nanostructure arrays in highly lossy Ge film, the absorber obtains a high absorptivity, reaching above 90% over the full visible wavelength, and it can be maintained well at a large viewing angle over 50°. Based on the geometrical symmetry, the absorber is proved to be polarization independent. Moreover, the simple single-sized nanostructure within a certain size tolerance decreases the design and fabrication complexity. The structural configuration with a slight Ge sidewall formed in the nanofabrication process could enhance the overall light absorption. These results indicate that the proposed broadband absorber has great potential in various applications such as anti-reflective coating and perfect cloaking.